The role of nursing committees in improving service quality and nurses' psychological well-being: A literature review - Hitipeuw, Ekklesia (JOURNAL OF Mental Health Concerns, 2026)
Background: The quality of nursing services is an important indicator of healthcare quality in hospitals. The nursing committee plays a strategic role in ensuring nurses’ professionalism through credentialing processes, competency development, and supervision of ethical and professional standards. Purpose: To review the role of nursing committees in improving the quality of nursing services based on previous research findings. Method: A narrative literature review approach. The reviewed articles were obtained from relevant national and international journals focusing on nursing committees and the quality of nursing services. Article selection was conducted based on relevance to the research topic and objectives, followed by systematic analysis and synthesis. Results: Nursing committees play a significant role in improving the quality of nursing services through credentialing and re-credentialing, professional development and coaching, and supervision of nursing practice standards and ethics. Optimizing the role of nursing committees contributes to improved nurses’ competence, performance, and professionalism, which in turn enhances the quality of nursing care and patient safety. Conclusion: Nursing committees have a strategic role in supporting the improvement of nursing service quality in hospitals. Continuous strengthening and evaluation of nursing committee functions are necessary to ensure optimal contributions to nursing service quality. Keywords: Literature Review; Nursing Committee; Nurse Professionalism; Quality of Nursing Services.